(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In recent years, a completely new system and reforms have been implemented in our country to strengthen the role and status of women in society, ensure their rights and freedoms, increase their socio-political activity, medical culture and intellectual potential, especially strengthening families. First of all, a new system has been created to improve the socio-spiritual environment in families and coordinate the activities of public organizations in this regard. In this article, we consider our proposals and recommendations to address this problem in the country today, based on the socioeconomic potential of the regions, demographic composition, employment, prevention of crimes involving women, the causes and other factors. we tried to find analytical solutions by summarizing the results of our research.